MiR-302b Suppresses Osteosarcoma Cell Migration and Invasion by Targeting Runx2. Issue 1 (December 2017) - Xie, Yuanlong; Sun, Wenchao; Deng, Zhouming; Zhu, Xiaobin; Hu, Chao; Cai, Lin
Abstract Osteosarcoma patients with lung metastasis and local invasion remain challenging to treat despite the significant contribution of the combination of surgery and neo-adjuvant chemotherapy. Our previous microarray study demonstrated that miR-302b had significantly lower expression in osteosarcoma cell lines than in osteoblast cell lines. In the present study, we further elucidated the role of miR-302b in regulating the migration and invasiveness of osteosarcoma. MiR-302b expression was markedly down-regulated in osteosarcoma cell lines and clinical tumour tissues. Lower levels of miR-302b expression were significantly associated with metastasis and high pathological grades. A functional study demonstrated that over-expression of miR-302b suppressed tumour cell proliferation, invasion and migrationin vitro andin vivo . Runx2 was identified as a direct target gene for miR-302b by bioinformatics analysis and dual-luciferase reporter gene assay. Moreover, over-expression of miR-302b induced down-regulation of Runx2, OPN, MMP-2, MMP-9, MMP-12, MMP-14, and VEGF in 143B cells. Exogenous expression of Runx2 partially rescued the inhibitory effect of miR-302b on the invasion and migration activity of 143B osteosarcoma cells. Taken together, our results indicate that miR-302b functions as a tumour repressor in the invasion and migration of osteosarcoma by directly downregulating Runx2 expression and may be a potential therapeutic target for osteosarcoma.